BASIC PSYCHOLOGICAL NEEDS, HAPPINESS AND PHYSICAL ACTIVITY: A STUDY WITH PUBLIC SERVANTS IN A STATE OF THE BRAZILIAN AMAZON - de Souza, Célio Roberto Santos; Dias, Helton Magalhães; Zanetti, Marcelo Callegari; Souza, Kátia Silene Silva; da Rocha Silva, Elyene Elene Meireles; de Sousa, Moisés Simão Santa Rosa; dos Santos, Marco Antônio Barros; Damasceno, Cícero Pereira Batista (Seven Editora, 2025)
Autonomy, competence and belonging are basic psychological needs (NPB), which can determine a good life when met. For adults of working age, workers responsible for attending services provided by the state, the satisfaction of NPBs in the context of life can determine the quantity and especially the quality of care needed by society. Due to the importance of this theme, the aim of this study was to associate the levels of BPN satisfaction in the general context of life with the indicators of happiness and the level of physical activity (PA). The study involved 108 individuals with a mean age of 31.86 years (SD ± 8.9). The instruments used to assess the happiness indicators were the psychological well-being scale (PWB), the life satisfaction scale (SWLS), the positive and negative affect scale (PANAS) and the PA level through the IPAC. The results indicate that people with high levels of NPB satisfaction have higher levels of happiness and physical activity.DOI: https://doi.org/10.56238/sevened2025.021-083